2022
DOI: 10.3390/pharmaceutics14081681
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Targeted Delivery of Novokinin as an Alternative Treatment Option for Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune inflammatory bone destructive disorder that is orchestrated by multiple systems in the body, including Renin-Angiotensin System (RAS) and arachidonic acid (ArA) pathway. Current therapeutic options are not highly effective and are associated with severe side effects, including cardiovascular complications. Therefore, new safe and effective disease modulators are seriously needed. In this study, we investigate the anti-inflammatory effects of a synthetic peptide, novok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…It has been reported that AT2R activation favors EETs production, inhibits pro-inflammatory cytokine intracellular signaling [ 52 ], and probably helps patients to recover from this viral infection. The anti-inflammatory effects of direct AT2R stimulation have been reported using selective peptide [ 35 ] and nonpeptide [ 53 ] AT2R agonists. These anti-inflammatory effects do not counteract Ang II-induced, AT1R-mediated pro-inflammatory actions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that AT2R activation favors EETs production, inhibits pro-inflammatory cytokine intracellular signaling [ 52 ], and probably helps patients to recover from this viral infection. The anti-inflammatory effects of direct AT2R stimulation have been reported using selective peptide [ 35 ] and nonpeptide [ 53 ] AT2R agonists. These anti-inflammatory effects do not counteract Ang II-induced, AT1R-mediated pro-inflammatory actions.…”
Section: Discussionmentioning
confidence: 99%
“…A liquid–liquid extraction (LLE) method using ethyl acetate was utilized to extract the ArA metabolites from the plasma samples. This method was previously validated in our lab [ 35 ]. Briefly, 300 µL of plasma sample was mixed with 100 µL of 10,11-EET d11 (IS, 100 ng/mL), and 2 µL of FA was added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients' plasma samples were analyzed for Ang 1-7 and Ang II levels by the published LC-MS/MS method [28]. The method was applied for plasma sample analysis after minor modification and validation.…”
Section: Lc-ms/ms Methods For Ang Peptidesmentioning
confidence: 99%
“…A liquid-liquid extraction (LLE) method using ethyl acetate was utilized to extract the ArA metabolites from the plasma samples. This method was previously validated in our lab [28]. Briefly, 300 µL of plasma sample was mixed with 100 µL of 10,11-EET d11 (IS, 100 ng/mL), and 2 µL of FA was added.…”
Section: Liquid-liquid Extraction (Lle)mentioning
confidence: 99%